Speech act of flaming in twitter status: issues and concerns in the Malaysian context / Norizah Ardi ... [et al.] - Ardi, Norizah; Ahmad, Amirah; Daud, Noriza; Ismail, Nurrissammimayantie (Universiti Teknologi MARA, 2020)
Speech acts are a way to conceptualize speech as an action. Speech act of flaming is an utterance that expresses insults; swearing; and hateful; intense language in hostile online interaction. Flaming is an expressive speech act and often leads to the trading of insults between members within a certain conversation. Social media is one of the platforms that has been used to express, comment and voice out emotions. In this study, the speech act of flaming in a Twitter status will be analysed based on the Malaysian context. The data of this study is a compilation of Twitter statuses consisting of 2.5 million words and is labelled as Malaysian Twitter Status Context corpus (MTSC). The tweets were analysed based on 14 subcategories of flaming (Bansal, Nittin, Siddhartha, Kapil, Anuj, Sheenu, Kanika, Kunal, Kunal, Manav, 2012 and Revathy & Norizah, 2017). This study adopted the qualitative approach through contextual analysis. Findings of this study showed that flaming in Malaysian context can be direct or intentional; and indirect based on the intentions (illocutionary force) to offend other tweeters. Findings of this study show that language usage among youngsters specifically the tweeters are not in line with the values and ethics that have been practiced in our culture and society.